Exchange rate regime and economic growth in Asia: Convergence or divergence - Dao Thi-Thieu Ha; Nga Thi Hoang (Journal of Risk and Financial Management, 2020)
Exchange rates and exchange rate regimes in a constantly changing economy have always attracted much attention from scholars. However, there has not been a consensus on the effect of exchange rate on economic growth. To determine the direction and magnitude of the impact of an exchange rate regime on economic growth, this study uses the exchange rate database constructed by Reinhart and Rogoff. This study also employs the GMM (Generalized Method of Moments) technique on unbalanced panel data to analyze the effect of the exchange rate regime on economic growth in Asian countries from 1994 to 2016. Empirical results suggest that a fixed exchange rate regime (weak flexibility) will affect economic growth in the same direction. As such, results from the study will serve as quantitative evidence for countries in the Asian region to consider when selecting a suitable policy and an exchange rate regime to attain high economic growth.
Keywords: 330; Asia; economic growth; exchange rate regime; Reinhart and Rogoff